Lewis B. Schwellenbach papers - Schwellenbach, Lewis B. (Lewis Baxter), 1894-1948.
Correspondence, speeches, writings, clippings, scrapbooks, and other papers relating primarily to Schwellenbach's service as U.S. senator from Washington (State) and U.S. secretary of labor in the Harry S. Truman presidential administration. Subjects include Schwellenbach's friendship with Truman, anti-alien legislation, anti-communism, civil liberties, Huey Long and the use of filibuster in the U.S. Senate, fishing and lumber industries in Washington (State), labor strikes, rights of the handicapped and veterans, the U.S. Labor Management Relations Act (Taft-Hartley Act of 1947), transition from a war-based to a peacetime economy, American neutrality in European wars, democracy in Spain and the Spanish Civil War (1936-1939), the rise of fascism under Adolph Hitler and Benito Mussolini, and U.S. relations with Japan. Correspondents include Frank T. Bell, John Nance Garner, Cordell Hull, Franklin D. Roosevelt, Harry S. Truman, and Schwellenbach's wife, Anne Duffy Schwellenbach.
U.S. secretary of labor, U.S. senator from Washington, jurist, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bell, Frank T. -- Correspondence; Garner, John Nance, -- 1868-1967 -- Correspondence; Hitler, Adolf, -- 1889-1945.; Hull, Cordell, -- 1871-1955 -- Correspondence; Long, Huey Pierce, -- 1893-1935.; Mussolini, Benito, -- 1883-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Schwellenbach, Anne Duffy -- Correspondence; Truman, Harry S., -- 1884-1972.; Truman, Harry S., -- 1884-1972 -- Correspondence; United States. -- Congress. -- Senate; United States. -- Congress. -- Senate -- Rules and practice; United States. -- Department of Labor; United States; Aliens -- United States; Anti-communist movements; Civil rights; Communism; Democracy -- Spain; Fascism; Filibusters (Political science) -- United States; Fisheries -- Washington (State); Forests and forestry -- Washington (State); Labor disputes; Neutrality -- United States; People with disabilities -- Government policy -- United States; Veterans -- Government policy -- United States; Japan -- Foreign relations -- United States; Spain -- History -- Civil War, 1936-1939.; United States -- Economic conditions -- 1945-; United States -- Economic policy -- 1945-1960.; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Europe; United States -- Foreign relations -- Japan; United States -- Politics and government -- 1901-1953.; Washington (State) -- Politics and government; Cabinet officers; Jurists; Lawyers; Senators, U.S. Congress -- Washington (State)